HUBUNGAN BERMAIN GAME ONLINE DENGAN GANGGUAN KESEHATAN MATA ANAK USIA DINI DI TK DHARMA WANITA PERSATUAN PROVINSI LAMPUNG - Asmi Asmi; Heny Wulandari; Kanada Komariah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Play online games more than 4 hours a day this includes the abnormal category because the normal category of children playing online games is (> 2 hours a day) this study aims to determine the relationship between playing games and eye health disorders in early childhood dharma wanita unity kindergaten, lampung province the formulation of problem in this research is there a relathionship between playing online game with eye health disorders in early chilhood.This type of research is quantitative research with cross sectional method. This type of research is to look at the relationship jbetween one variable and another. Data collection techniques jused are through questionnaires, Observations, and documentation. The population in this study were 24 children in the dharma wanita unity kindergaten in lampung province. The sample in this study were 24 children using purposive sampling technique. Based on the results of data analysis, it is known that there is a maderate and significant relationship between playing online games with health problems with a corelation value of 0,517 and sig 0,01 < 0,05. The relationship that occurs in positive or unidirectional, so that if children often play online games the higher the chance that the child will experience eye helath problems.